(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Endometriosis is a chronic, estrogen-dependent inflammatory disease characterized by the presence of endometrium-like tissue outside the uterine cavity, affecting up to 10–15% of women of reproductive age worldwide [24, 14]. It is among the leading causes of chronic pelvic pain and remains one of the most common gynecological disorders, associated with a marked decline in quality of life and a substantial socio-economic burden [24, 14]. Despite a certain decrease in incidence reported in some regions, endometriosis continues to represent a major medical and public health challenge due to delayed diagnosis, pronounced clinical and molecular heterogeneity, and the limited effectiveness of currently available therapeutic approaches. Diagnostic delay often reaches 7–10 years, thereby facilitating disease progression, chronicity of inflammation, and the development of resistance to hormonal therapy [14, 12]. Contemporary concepts of endometriosis pathogenesis have evolved considerably—from isolated anatomical theories to an understanding of the condition as a systemic disorder driven by a complex interplay of hormonal dysregulation, immune inflammation, oxidative stress, and genetic and epigenetic alterations [17, 14]. A central element of this multi-level pathogenic cascade is local hyperestrogenism, resulting from autonomous estrogen synthesis within endometriotic lesions and altered sensitivity of target tissues to steroid hormones.